A SUBJECT OF STUDY OF THE SOCIAL COMPONENT OF THE LANGUAGE IMAGE OF A PERSON (BASED ON THE MATERIAL OF THE RUSSIAN LANGUAGE) - Malokhat Turavaevna Yunusova (Web of Journals Publishing, 2023)
The article discusses the importance of studying phraseological units, proverbs, sayings, as a social component of a person’s linguistic image. An analysis of proverbs in Russian language dictionaries was carried out, which made it possible to identify proverbs and sayings of the thematic group “Man, his character and abilities. Language. Intelligence. Science”, revealing and describing not only the moral system of human values, but also the properties, scientific characteristics of language, human character traits that act as the language of culture, and also highlight three groups of proverbs and sayings. Various definitions of the terms “proverb” and “saying” in modern linguistics are considered, their differences between each other, the way of expressing judgments, the presence of literal and figurative meanings and their significant dissimilarity from phraseological units. The analysis of phraseological units, proverbs and sayings of the selected thematic group is generalized.
Keywords: proverbs, phraseological unit, proverb, saying, polysemy of the Russian proverb, semantic property, aphorism, oral and written speech.